2007
DOI: 10.1063/1.2787872
|View full text |Cite
|
Sign up to set email alerts
|

Flow around a confined rotating cylinder at small Reynolds number

Abstract: A numerical finite-volume technique to solve the two-dimensional Navier-Stokes equations is applied to the rotation of a rigid circular cylinder between parallel plane walls. In this confined situation, the torque exerted on the cylinder is a function of both the distance between the two walls and the position between them. In the absence of experimental results for this problem, we propose here new data of the torque in a wide range of confinements and we study the influence of the eccentricity of the cylinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…For this case, a rotating (translating) cylinder experiences no force (torque). However, recent computational analysis has shown that the presence of a second wall leads to a net force on a purely rotating cylinder [13]. We have analyzed this problem using lubrication theory and numerical analysis [14,15] and have found that the force on the rotating cylinder arises from the constraint that the volume flux of fluid in the gap above the cylinder must equal the flux of fluid through the lower gap.…”
mentioning
confidence: 99%
“…For this case, a rotating (translating) cylinder experiences no force (torque). However, recent computational analysis has shown that the presence of a second wall leads to a net force on a purely rotating cylinder [13]. We have analyzed this problem using lubrication theory and numerical analysis [14,15] and have found that the force on the rotating cylinder arises from the constraint that the volume flux of fluid in the gap above the cylinder must equal the flux of fluid through the lower gap.…”
mentioning
confidence: 99%
“…This results from the backflow near the second wall and has a sizable influence on the force distribution on the cylinder. 10 The displacement of a free cylinder released from an eccentric position inside a vertical gap has been computed by Hu 6 for three values of the Reynolds number Re based on the terminal velocity and the diameter of the particle. For Re ≤ 5, the cylinder reaches a final stable transverse position in the middle of the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, 1.5-3 channel widths on each side of the particle are sufficient for the calculated characteristics to be independent of channel length." A few cases were implemented to validate the numerical results presented in Champmartin et al, 13 and consistent results were obtained. The numerical solutions obtained with COMSOL were therefore employed as a reference solution for comparison with the corresponding lubrication and scaling solutions.…”
Section: Resultsmentioning
confidence: 99%
“…It is perhaps then even more surprising that the force deviates from zero as a second wall (see Figure 3(b)), parallel to the first, is brought in from infinity. 13 As we shall see in the three geometries of Figure 2, the presence of a new boundary affects the previous interactions in a nontrivial, non-additive way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation